Individual-level explanations of corruption within an intercollegiate context - Kihl, Lisa (Journal of Intercollegiate Sport, 2019)
Understanding why individuals engage in sport corruption is an emerging topic of research. Micro-level accounts of corruption have generally used a single disciplinary approach toward understanding why actors commit corruption (e.g., doping and match-fixing) in specific sports. The purpose of this study was to first examine individual-level explanations of corruption in the context of intercollegiate athletics; and, second, to generate an interdisciplinary framework. A multi-case analysis was conducted of 20 National Collegiate Athletic Association (NCAA) major infractions (corruption) reports that occurred between 2005 and 2015. The findings showed that actors’ explanations were based on psychological factors—motivations (social relationship and self-interest) and personal norms, professional factors (abuse of power and failure of responsibilities), and justification factors (rationalizing strategies). This research builds on existing scholarship by generating an interdisciplinary framework of micro-level accounts of sport corruption in intercollegiate athletics.